Eco-innovation and International Competitiveness of Enterprises Results for European Union Member States - Małgorzata Stefania Lewandowska (Comparative Economic Research. Central and Eastern Europe, 2020)
Intensive global warming, declining natural resources, and pollution are the factors influencing the wider debate about what creates a "green economy." Taking the above into account, the purpose of this paper is to present an overview of the eco-innova-tion performance of European Union members and, at the same time, their overall level of innovativeness. The paper also provides insights into the role of eco-inno-vation as the driving force for the international competitiveness of enterprises from European Union countries. The results at the macro level show that there is a strong interdependence between the level of innovativeness and the level of eco-innovation implementation in the EU Member States. In turn, the micro-analysis conducted for EU enterprises shows that there is an interdependence between the introduction of eco-innovation with benefits for the end-user and the level of international competi-tiveness measured by the intensity of exports. Enterprises from countries with a high-er overall Innovation Union Scoreboard (IUS) and Eco-Innovation Scoreboard (Eco-IS) are simultaneously characterized by a higher intensity of eco-innovation, introducing benefits for the end-user, and an intensive presence with sales on foreign markets. Enterprises from countries with low IUS and Eco-IS rankings, including the countries of Central and Eastern Europe, are characterized by a relatively low intensity of intro-ducing eco-innovation accompanied by a relatively low export intensity.
Keywords: F64; O32; O44; 330; Eco-innovation; International competitiveness; Innovation Union Scoreboard; Eco-Innovation Scoreboard; Community Innovation Survey (CIS)